THE STUDENTS’ PERCEPTION OF BRITISH AND AMERICAN CULTURES IN SENIOR HIGH SCHOOL INTERLANGUAGE ENGLISH TEXTBOOK (This Case Study at One of Senior High School in Garut) - Euis Patimah (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
Awareness of the existence of foreign cultures in Indonesia in various fields, especially in the field of education, that the influence of foreign cultures can have positive and negative effects on school students. What is meant by cultural awareness is Cultural Awareness: An introduction to the nuances of one's own culture and that of other cultures. Cultural Competence: The ability of individuals to use academic, experiential, and interpersonal skills to enhance their understanding and appreciation of cultural differences and similarities within, between, and between groups. This study aims to understand cultural awareness and the impact of foreign culture on students in schools. Qualitative methods used through observation and interviews and semi-structured observation. The participants in this study were six twelfth grade students consisting of three girls and three boys at a high school in Garut. Findings found in this study are the perceptions of students who study English Interlanguage books, namely that there are many learning cultures that can be imitated because they bring positive things and improve student learning values and can also motivate students to be more critical of cultural awareness.